Correlation between atherogenic index of plasma and national institutes of health stroke scale score in acute ischemic stroke patients at Haji Adam Malik general hospital, Medan - Zulfikri, Muhammad; Arina, Cut A.; Batubara, Chairil A. (International Journal of Research in Medical Sciences, 2021)
Background: Stroke is the leading cause of morbidity and mortality in Indonesia. Dyslipidemia is one of the main risk factors of ischemic stroke. Atherogenic index of plasma (AIP) is the logarithm of the triglyceride’s plasma ratio concentration to high density lipoprotein cholesterol (HDL-C) plasma concentration. Previous studies showed that the high AIP at hospital admission was associated with deterioration of neurological deficits in patients with acute ischemic stroke. Methods: This is a cross sectional study with 82 sample of acute ischemic stroke subjects that consecutively collected from the medical records of Haji Adam Malik general hospital Medan from January to December 2019, AIP assessment performed at the 1st day of hospitalization and then at the 7th -onset the national institutes of health stroke scale (NIHSS) score assessment was count. Data analysis is conducted with Spearman test. Results: Demographic characteristics showed that most subjects were female (51.2%), at age range between 60 -68 years (30.5%), had high school education level (48.8%), self-employed (35.4%) and Bataknese (68.3%). The mean of AIP was 0.15±0.26 and the mean NIHSS score was 6.70±3.6. There was a positive significant and mild power of correlation between AIP and the NIHSS score (p=0.017; r=0.262). Conclusions: There is a significant relationship between AIP and the NIHSS score. The higher the AIP of acute ischemic stroke patients was associated with the increase in the NIHHS scores.